Problem-Solving Approach of Bhabinkamtibmas in Fostering Community Security and Order in Kuning Gading Hamlet, Pelepat Ilir Subdistrict, Bungo Regency - Harpin Syah; Ronal Dison; M. Darmawi (Jurnal Ragam Pengabdian, 2026)
This study examines the problem-solving approach employed by Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (Bhabinkamtibmas) in fostering community security and order in Kuning Gading Hamlet, Pelepat Ilir Subdistrict, Bungo Regency, employing qualitative methods including observation, in-depth interviews, and documentation with 8 purposive informants (subdistrict police chief, Binmas unit head, hamlet leader, community figures, and residents). Primary approaches encompass door-to-door visits, face-to-face patrols, kamtibmas information dissemination via posters and outreach, cross-sectoral coordination with hamlet government and customary institutions, and musyawarah mediation for domestic violence (KDRT: 6 cases, 4 reconciled), land disputes (4 cases, 3 successful), traffic accidents (2 cases, 2 successful), assaults (2 cases, 2 successful), and theft (1 case, 1 successful) in 2022-2023. Supporting factors include Kapolri policies (Perkapolri No. 3/2015 on Community Policing), Bhabinkamtibmas competencies, available reporting software, hamlet and community leader support, and IT advancements; barriers involve low public trust in police, limited legal awareness, problem concealment, outdated disruption intelligence, and personnel/facility shortages (1 officer for 3,483 residents). Findings confirm the efficacy of problem-solving as a contextual Problem-Oriented Policing (POP) strategy for preventing social conflict escalation in transmigration areas, achieving 87% mediation success (13/15 cases).